Adaptive UI/UX Evaluation of BufferSee AR Using SUS - Ketut Sepdyana Kartini; I Nyoman Tri Anindia Putra (Yayasan Sinergi Widya Nusantara (Sidyanusa), 2026)
This study aimed to develop and evaluate an adaptive UI/UX design for BufferSee AR, an augmented reality-based mobile learning application designed to support chemistry learning, particularly buffer solution material. The initial version of BufferSee AR already provided several learning features, including AR Camera, learning materials, practice questions, quizzes, user guidance, marker download, and 3D visualization. However, usability issues were identified in the early interface, particularly in navigation clarity, icon consistency, learning flow, user guidance, and accessibility for students with different levels of digital literacy. This research employed the ADDIE development model consisting of Analysis, Design, Development, Implementation, and Evaluation. The usability evaluation was conducted using the System Usability Scale (SUS) involving 30 student respondents. The evaluation results showed that the initial version obtained an average SUS score of 55, categorized as Marginal. After adaptive UI/UX redesign, the average SUS score increased to 82.5, categorized as Acceptable/Good. These findings indicate that adaptive UI/UX design improved efficiency, effectiveness, and user satisfaction in using BufferSee AR as an interactive chemistry learning medium.